Fiber Optic and Laser Sensors VIII 1991
DOI: 10.1117/12.24753
|View full text |Cite
|
Sign up to set email alerts
|

Fiber optic sensor for simultaneous measurement of strain and temperature

Abstract: We propose polarimetric and two-mode differential interferometric schemes incorporated in an elliptical-core fiber to resolve strain and temperature simultaneously. Initial results indicate accuracies of 10 jim/m and 5°C for strain and temperature measurements, respectively. A technique, based on the evaluation of the condition number of a matrix, is shown to be useful in evaluating comparative merits of multiparameter sensing schemes. Experimental results for four fibers are presented and cross-sensitivity is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

1993
1993
2000
2000

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(11 citation statements)
references
References 8 publications
0
11
0
Order By: Relevance
“…This issue is, of course, an important consideration for many types of sensors, and a number of approaches [62][63][64] had been previously demonstrated using dual modes, two polarizations, and dual wavelength interrogation. These approaches in general produce output responses which exhibit normalized responsivity factors that are only fractionally different and thus perform poorly at separating strain and temperature perturbations.…”
Section: Low-coherence Interferometrymentioning
confidence: 99%
“…This issue is, of course, an important consideration for many types of sensors, and a number of approaches [62][63][64] had been previously demonstrated using dual modes, two polarizations, and dual wavelength interrogation. These approaches in general produce output responses which exhibit normalized responsivity factors that are only fractionally different and thus perform poorly at separating strain and temperature perturbations.…”
Section: Low-coherence Interferometrymentioning
confidence: 99%
“…In any expression involving more than one material, the material properties will be subscripted, with subscript 1 corresponding to the fiber and each higher subscript conesponding to the next outer material layer. The superscript (1) refers to the number of material layers in the structure. A member made of a single material (E,vi), either a bare fiber or a member with no embedded fiber, has…”
Section: Axisymmetric Loadsmentioning
confidence: 99%
“…It has been demonstrated that the Bragg wavelength, Xb, is related to the grating pitch, A, and the average refractive index ne, by kb = 2neA. (3) It has been further shown that this wavelength will shift by an amount Akb as a function of the strain and temperature as…”
Section: Bragg Grating Sensorsmentioning
confidence: 98%